Hormonal Induction Of Ovarian Cyclicity And Conception Rate In Postpartum Anestrus Buffaloes - Ali, Rameez; Shukla, S.P.; Nema, S.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Therapeutic efficacy of Ovsynch, Heat synch and CIDR hormone protocols in terms of estrus induction efficiency, estrus induction interval and conception rate were judged in 24 postpartum anestrus buffaloes. The buffaloes in treatment group A, B and C were subjected to Ovsynch, Heat synch and CIDR hormone protocols respectively. Response of anestrus buffaloes to different hormonal treatments in terms of estrus induction efficiency was 50, 100 and 83.33 per cent with a mean post treatment estrus induction intervals of 18.67 ±3.18, 12.75 ± 1.86 and 15.60 ± 2.35 hrs in these hormone protocols respectively from the last parentral administration of the drug. Further, in Ovsynch, Heat synch and CIDR protocols the conception rate was 33.33, 50.00 and 60.00 per cent respectively.
Keywords: Ovsynch; Heat-synch; CIDR; Buffaloes; Estrus induction; Conception rate